Algae as promising feedstocks for fermentative biohydrogen production according to a biorefinery approach: A comprehensive review. (April 2015) - Sambusiti, Cecilia; Bellucci, Micol; Zabaniotou, Anastasia; Beneduce, Luciano; Monlau, Florian
Abstract: Interest is growing in the production of biohydrogen from algae through dark fermentation, as alternative to fossil fuels. However, one of the limiting steps of biohydrogen production is the conversion of polymeric carbohydrates into monomeric sugars. Thus, physical, chemical and biological pretreatments are usually employed in order to facilitate carbohydrates de-polymerization and enhancing biohydrogen production from algae. Considering the overall process, biohydrogen production through dark fermentation leads generally to negative net energy balances of the difference between the energy produced as biohydrogen and the direct ones (heat and electricity) consumed to produce it. Thus, to make the overall process economically feasible, dark fermentation of algae must be integrated in a biorefinery approach, where the outlets are valorized into bioenergy or value added biomolecules.The present study reviews recent findings on pretreatments and biohydrogen production through dark fermentation of algae looking at the perspectives of integrating side streams of dark fermentation from algal biomass, according to a biorefinery approach.